Regulation profile of the intestinal peptide transporter 1 (PepT1) - Wang CY; Liu S; Xie XN; Tan ZR (Dove Medical Press, 2017)
Chun-Yang Wang,1,2 Shu Liu,1,2 Xiao-Nv Xie,1,2 Zhi-Rong Tan1,2 1Department of Clinical Pharmacology, Xiangya Hospital, Xiangya School of Medicine, Central South University, 2Hunan Key Laboratory of Pharmacogenetics, Institute of Clinical Pharmacology, Central South University, Changsha, Hunan, People’s Republic of China Abstract: The intestinal peptide transporter 1 (PepT1) was first identified in 1994. It plays a crucial role in the absorption of small peptides including not only >400 different dipeptides and 8,000 tripeptides digested from dietary proteins but also a repertoire of structurally related compounds and drugs. Owing to its critical role in the bioavailability of peptide-like drugs, such as the anti-cancer agents and anti-virus drug, PepT1 is increasingly becoming a striking prodrug-designing target. Therefore, the understanding of PepT1 gene regulation is of great importance both for dietary adaptation and for clinical drug treatment. After decades of research, it has been recognized that PepT1 could be regulated at the transcriptional and post-transcriptional levels by numerous factors. Therefore, the present review intends to summarize the progress made in the regulation of PepT1 and provide insights into the PepT1’s potential in clinical aspects of nutritional and drug therapies. Keywords: PepT1, dietary, regulation, transport activity, absorption, bioavailability